ミクログリアによるATP/P2Y1シグナルを介したニューロン-アストロサイト間情報伝達の制御 - 鈴木, 秀明; 小泉, 修一; 高橋, 由香里; 加藤, 総夫; 尾藤, 晴彦; 田中, 謙二; 繁冨, 英治; 池中, 一裕; 平山, 幸歩 (日本薬理学会年会要旨集, 2022)
P2Y1 receptor is upregulated in astrocytes in many neurological diseases. We have previously shown that elevated P2Y1 receptor expression in astrocytes causes neuronal hyperexcitability by enhancing neuron-astrocyte communication in the hippocampal CA1 region. However, contribution of microglia to the astrocytic P2Y1 receptor-mediated neuron-astrocyte communication is not known, despite the fact that microglia are also activated in such pathological conditions. To this end, we attempted to investigate the role of microglia in astrocyte P2Y1 receptor signaling by depleting microglia with a CSF1 receptor antagonist, PLX5622. The results are summarized in the following two points: 1) Microglia depletion increased P2ry1 gene expression in astrocytes and enhanced Ca2+ signal via P2Y1 receptor, indicating that microglia would have a role to inhibit P2Y1 receptor expression in astrocytes. 2) Microglia depletion prolonged the time required for degradation of exogenously applied ATP. Because microglia highly express an ATP degrading enzyme CD39, they would play a central role in shutting-off of P2Y1 receptor signals by metabolizing ATP. Taken together, it is suggested that microglia would also play an important role in neuron-astrocyte communication via 2 different modes, i.e., inhibition of P2Y1 receptor expression and degradation of extracellular ATP.